(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1869)
This paper examines tombstones and crosses found in the West Highlands. The author explains that some of these monuments have been moved from their original locations and others, such as the tombstones in Kilmartin, have been deliberately damaged. He also notes that monuments on Iona have been placed upside down and briefly comments on the common symbols found on medieval tombstones in these locations.